High-flow-state negative carbon auxiliary cementing material prepared based on carbonization reconstruction process
By utilizing wind power to prepare highly fluid negative carbon auxiliary cementitious materials in a humidity and CO2 environment, the problem of resource application of RCF in the building materials field was solved, efficient CO2 storage and material performance improvement were achieved, and the water absorption and fluidity limitations of RCF were broken through.
Patent Information
- Application Number
- CN202510798779.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-16
- Publication Date
- 2025-09-16
AI Technical Summary
In existing technologies, the recycled concrete fines (RCF) produced by building demolition are limited in their resource application in the building materials field due to their high porosity, strong water absorption and low cementing activity. In addition, the traditional wet carbonization process requires a large amount of water, has low efficiency, and the product has high water absorption, which affects concrete construction.
Using the carbonization reconstruction process, in an environment with a humidity of 60-80% and a CO2 concentration of 10-20 vol.%, the moist RCF particles are carbonized in a suspended state by wind to form a dense calcium carbonate shell. The morphology and distribution of the carbonization products are regulated to prepare a highly fluid negative carbon assisted cementitious material.
It significantly reduces the water absorption rate of RCF particles, improves the fluidity of the material and the CO2 storage rate, saves water resources, realizes efficient RCF resource utilization, and has both low-carbon and high-performance construction performance.
Smart Images

Figure CN120647180A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of construction solid waste recycling and low-carbon building materials, and in particular to a high-fluidity negative carbon auxiliary gelling material prepared based on a carbonization reconstruction process. Background Art
[0002] Waste concrete from building demolition is a major source of solid waste, with recycled concrete fines (RCF) accounting for over 30%. RCF's high porosity, strong water absorption, and low cementing activity severely restrict its resource utilization in the building materials sector. Consequently, traditional RCF disposal methods primarily rely on landfill or low-value utilization.
[0003] In the field of low-carbon building materials technology, carbonization and modification of industrial solid waste is considered an effective way to achieve CO2 storage and synergistic improvement of material properties. In recent years, researchers have attempted to achieve CO2 storage and RCF activity improvement through wet carbonation or mechanical activation carbonation. However, the process is complex, requires a huge amount of water (water-to-solid ratio > 3), and produces a large amount of wastewater. In addition, the calcium-rich phase decalcifies after carbonization, resulting in the exposure of a large amount of highly absorbent silicon-rich phase. When used as a cementitious material in concrete (to replace cement), the slurry fluidity will be significantly deteriorated, which is not conducive to concrete construction.
[0004] In response to the above technical bottlenecks, it is urgent to develop a low-water-consumption, high-efficiency RCF carbonization modification method that can achieve efficient CO2 storage while breaking through the performance limitations of RCF's high water absorption and poor fluidity by regulating the morphology and distribution of carbonization products. Summary of the Invention
[0005] The purpose of the present invention is to provide a high-fluidity negative carbon auxiliary gelling material prepared based on a carbonization reconstruction process to solve the problems existing in the above-mentioned prior art.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is a method for preparing a high-fluidity negative carbon-assisted gelling material (i.e., a method for preparing a high-fluidity negative carbon-assisted gelling material using a carbonization reconstruction process), comprising the following steps:
[0008] The wet RCF particles are placed in an environment with a humidity of 60-80% and a CO2 concentration of 10-20 vol.%, and the wet RCF particles are carbonized in a suspended state by wind (i.e., CO2 reacts with Ca(OH)2 on the RCF surface) to obtain the highly fluid negative carbon assisted gelling material.
[0009] Furthermore, the moisture content of the wet RCF particles is 8 to 12 wt.%;
[0010] The wind speed is 100-300m 3 / h;
[0011] The carbonization reaction time is 0.5 to 1 hour;
[0012] The particle size of the RCF particles is ≤150 μm.
[0013] The surface of the high-fluidity negative carbon-assisted cementitious material obtained by carbonization has a calcium carbonate shell layer with a thickness of 10 to 15 μm (the calcium carbonate shell layer coverage is 100%, tightly covering the surface of the RCF particles). The calcium carbonate shell layer is formed during the carbonization process. The calcium carbonate shell layer formation process is as follows:
[0014] (a) Dissolution mass transfer stage: CO2 diffuses through the liquid film on the particle surface to the RCF interface, and calcium ions dissolve from the RCF and migrate into the liquid film on the particle surface;
[0015] (b) Heterogeneous nucleation stage: CO2 and Ca 2+ Nano-calcium carbonate crystal nuclei are formed on the surface of RCF;
[0016] (c) Crystal growth stage: The crystal nucleus preferentially grows into a continuous calcite shell, i.e., a calcium carbonate shell, along the crystal surface.
[0017] The specific surface area of the high-fluidity negative carbon auxiliary gelling material obtained after the treatment of the present invention is 350-450m 2 / kg, which is 15-25% lower than that of the raw material RCF particles; the standard consistency water requirement of the high-fluidity negative carbon auxiliary gelling material obtained after the treatment of the present invention is 22-24%, which is lower than 26-28% of the raw material RCF particles.
[0018] The bulk density of the high-fluidity negative carbon auxiliary gelling material is 1.03-1.15 g / cm 3 , CO2 storage rate is 20~25wt.%.
[0019] The high-fluidity negative carbon auxiliary gelling material has a 60-minute water absorption rate of ≤5.5%.
[0020] The mechanism of action of the present invention:
[0021] Dynamic interface renewal mechanism (dynamic carbonization environment): Wind action can cause RCF particles to continuously roll, exposing fresh reaction interfaces; at the same time, the mass transfer efficiency under wind action is significantly improved compared to the wet method;
[0022] Shell directional growth control: Semi-dry environment (humidity 60-80%) can form a water film to regulate Ca 2+Dissolution and CO3 2- diffusion, ultimately inducing calcium carbonate to grow along the surface of RCF particles, forming a continuous calcium carbonate shell;
[0023] Mechanism of synergistic performance improvement: The larger the specific surface area, the higher the water absorption rate. The continuous, low-hydrophilic calcium carbonate shell formed by the present invention has the function of repairing the cracks and original fissures of RCF particles, reducing the specific surface area and capillary water effect of RCF particles, thereby achieving the purpose of optimizing fluidity while reducing water absorption rate.
[0024] The second technical solution of the present invention: a high-fluidity negative carbon auxiliary gelling material prepared by the above preparation method.
[0025] The third technical solution of the present invention: an application of the above-mentioned high-fluidity negative carbon auxiliary cementitious material in the preparation of concrete.
[0026] The high-fluidity negative carbon auxiliary cementitious material can ensure the fluidity of cement mortar when replacing 15 to 30 wt.% of cement.
[0027] When the high-fluidity negative carbon auxiliary cementitious material replaces 15 wt.% of cement, the fluidity of the cement paste can be improved by 13-15%, and the 28-day mechanical properties do not decrease significantly.
[0028] Technical solution 4 of the present invention: A method for reducing the water absorption of RCF particles, wherein the RCF particles are modified, comprising the following steps:
[0029] The wet RCF particles are placed in an environment with a humidity of 60-80% and a CO2 concentration of 10-20 vol.%, and the wet RCF particles are carbonized in a suspended state by wind.
[0030] Technical solution 5 of the present invention: A method for improving the fluidity of RCF particles, wherein the RCF particles are modified, comprising the following steps:
[0031] The wet RCF particles are placed in an environment with a humidity of 60-80% and a CO2 concentration of 10-20 vol.%, and the wet RCF particles are carbonized in a suspended state by wind.
[0032] Furthermore, the moisture content of the wet RCF particles is 8 to 12 wt.%;
[0033] The wind speed is 100-300m 3 / h;
[0034] The carbonization reaction time is 0.5 to 1 hour;
[0035] The particle size of the RCF particles is ≤150 μm.
[0036] The present invention discloses the following technical effects:
[0037] (1) The method of the present invention solves the problems of large water demand, low carbonization efficiency and high water absorption of the product in the existing wet carbonization process, and solves the problem of poor fluidity in preparing cement mortar with RCF particles.
[0038] (2) The method of the present invention breaks through the limitation of the traditional wet carbonization water-solid ratio of more than 3, and achieves efficient carbonization at a water-solid ratio of 0.08 to 0.12, significantly saving water resources and achieving zero wastewater discharge; through wind action (wind fluidization) and humidity coupling control (continuously inputting a mixed gas rich in water and CO2 through wind action to promote rapid carbonization of RCF), the carbonization reaction time is shortened from 6 hours (carbonization time under static state) to 0.5 to 1 hour; and the prepared high-fluidity negative carbon auxiliary cementitious material has a dense calcium carbonate shell, which can make the material's 60-min water absorption rate ≤5.5%; when the high-fluidity negative carbon auxiliary cementitious material is used to replace 15wt.% of cement, the fluidity of the cement slurry can be increased by 13 to 15%, and the mechanical properties have no obvious decrease, with both construction performance and ecological benefits, providing a low-carbon and high-performance solution for the resource utilization of construction solid waste.
[0039] (3) The method of the present invention can achieve a CO2 storage rate of 20-25% (i.e., 0.20-0.25 kg of CO2 is stored per kg of RCF), which is similar to the traditional wet carbonization process. The bulk density of the prepared high-fluidity negative carbon auxiliary cementitious material is 1.03-1.15 g / cm 3 It can maintain loose particles and avoid particle agglomeration caused by water film. It does not require dry grinding and can directly meet the application requirements of cementitious materials. Compared with the traditional wet carbonization process, it saves energy consumption for filtering and drying. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0041] Figure 1 Schematic diagram of the structure and operation of the wind-powered suspension dynamic carbonization device used in the present invention, wherein 1 is the variable frequency fan, 2 is the lower screen, 3 is the RCF particles, 4 is the reaction chamber, 5 is the upper screen, 6 is the CO2-humidity coupling control system, 7 is the CO2 flow meter, and 8 is the CO2 cylinder;
[0042] Figure 2Figures depicting the microstructures of the raw materials and products used in Example 1 and Comparative Example 1, where (a) is a scanning electron microscope (SEM) image of RCF particles before carbonization; (b) is a scanning electron microscope (SEM) image of the highly fluid negative carbon-assisted gelling material prepared in Example 1; and (c) is a scanning electron microscope (SEM) image of the negative carbon-assisted gelling material prepared in Comparative Example 1 using conventional wet carbonization.
[0043] Figure 3 The particle size distribution diagram of the RCF particles used in Example 1, the high-flow negative carbon-assisted gelling material prepared in Example 1, and the negative carbon-assisted gelling material prepared in Comparative Example 1 (i.e., the traditional wet negative carbon-assisted gelling material), wherein (a) is the RCF particles, (b) is the high-flow negative carbon-assisted gelling material prepared in Example 1, and (c) is the negative carbon-assisted gelling material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0045] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any intermediate value within a stated value or stated range and any other stated value or intermediate value within the stated range is also encompassed by the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.
[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.
[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be exemplary only.
[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0049] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in this field and are not the focus of the present invention.
[0050] The wind-powered suspension semi-dry process device used in the specific embodiment of the present invention is composed of a double-layer screen system, a reaction chamber and an intelligent control module.
[0051] The double-layer screen system consists of a lower screen (200-mesh stainless steel screen) and an upper screen (300-mesh anti-escape screen). The lower screen is placed at the lower end of the reaction chamber, and the upper screen is placed at the upper end of the reaction chamber, connected to the reaction chamber to form a fluidized reaction zone with adjustable volume.
[0052] The intelligent control module consists of a variable frequency fan (air volume accuracy ± 5m 3 / h, which can adjust the suspension strength in real time) and a CO2-humidity coupling control system (accuracy: humidity ±2%, CO2 ±0.5vol.%, to ensure a stable reaction environment);
[0053] The variable frequency fan is placed at the bottom of the reaction chamber and is used to deliver wind power to the fluidized reaction zone;
[0054] The CO2-humidity coupling control system is connected to the CO2 cylinder via a pipeline, and a CO2 flow meter is provided on the pipeline;
[0055] The CO2-humidity coupling control system integrates a humidity adjustment module.
[0056] The reaction chamber is made of polycarbonate.
[0057] Example 1
[0058] A highly fluid negative carbon-assisted cementitious material made based on a carbonization reconstruction process:
[0059] (1) Take a stainless steel mesh with an aperture of 200 mesh as the lower mesh 2, place it on the lower end of the reaction chamber 4 (a transparent reaction chamber made of polycarbonate with a diameter of 5 cm) and connect it to the reaction chamber 4, spread 300 g of wet RCF particles 3 on the lower mesh 2 of the reaction chamber 4, take an upper mesh 5 with an aperture of 300 mesh (anti-escape mesh) and place it on the upper end of the reaction chamber 4 and connect it to the reaction chamber 4 to form a fluidized reaction zone with adjustable volume;
[0060] The wet RCF particles were prepared by crushing and magnetically separating construction demolition waste and then grinding it to a particle size of 48 to 75 μm to obtain RCF particles. The chemical composition of the RCF particles was determined, and the results are shown in Table 1.
[0061] Table 1 Chemical composition of RCF particles (wt.%)
[0062] Element CaO <![CDATA[Al2O3]]> <![CDATA[SiO2]]> MgO other content 64.75 4.96 19.81 4.0 6.48
[0063] Deionized water and RCF particles were mixed at a liquid-to-solid ratio (mass ratio) of 1:10 and mechanically stirred to obtain wet RCF particles.
[0064] (2) Set the variable frequency fan 1 (air volume accuracy ±5m 3 / h) placed at the bottom of the reaction chamber 4;
[0065] Among them, the variable frequency fan 1, the lower screen 2, the RCF particles 3, the reaction chamber 4 and the upper screen 5 are all placed in a CO2-humidity coupling control system 6 (accuracy: humidity ±2%, CO2 ±0.5vol.%, integrated humidity adjustment module). The CO2-humidity coupling control system 6 is connected to the CO2 cylinder 8 through a pipeline, and a CO2 flowmeter 7 is provided on the pipeline for adjusting the CO2 concentration.
[0066] (3) Start the device and set the air volume to 200m 3 / h, so that the wet RCF particles are in a suspended state (forming a suspended fluidized bed layer), the height of the suspended fluidized bed layer is maintained at 70% of the effective height of the cavity, the ambient temperature is 20°C, the ambient humidity is 60%, and the CO2 concentration is 15vol.%; the wet RCF particles are carbonized (carbonization time is 0.5h) to obtain a highly fluid negative carbon assisted gelling material.
[0067] The structure and operation diagram of the wind-powered suspension dynamic carbonization device used in this embodiment are shown in FIG. Figure 1 .
[0068] The bulk density of the high-fluidity negative carbon-assisted gelling material prepared in this example is 1.08 g / cm 3 , the CO2 storage rate is 28.25wt.%.
[0069] The surface of the high-fluidity negative carbon assisted cementitious material prepared in this embodiment has a dense calcium carbonate shell with a thickness of 10 to 15 μm (the shell coverage rate observed by SEM is 100%). The proportion of calcium carbonate (calcite-type calcium carbonate) determined by TG (i.e., the proportion of calcite-type calcium carbonate in the mass of RCF particles) is 54.11 wt.%.
[0070] Comparative Example 1
[0071] Preparation of negative carbon assisted cementitious materials by traditional wet carbonization:
[0072] Deionized water and RCF particles (same as in Example 1) were mixed in a liquid-to-solid ratio (mass ratio) of 5:1 to form a slurry. At 20°C, CO2 gas with a concentration of 15 vol.% was introduced at a flow rate of 3 L / min. After carbonization for 1 hour, the mixture was filtered and dried to obtain a negative carbon-assisted gelling material.
[0073] The bulk density of the negative carbon assisted gelling material prepared in this comparative example is 0.85 g / cm 3 , the CO2 storage rate is 30.38wt.%.
[0074] The surface of the negative carbon-assisted cementitious material prepared in this comparative example does not form a dense calcium carbonate shell, but adsorbed calcium carbonate particles, so it has a high water absorption capacity; the proportion of calcium carbonate (calcite-type calcium carbonate) determined by TG (the proportion of calcite-type calcium carbonate in the mass of RCF particles) is 56.95wt.%.
[0075] The microstructure characterization diagrams of the raw materials and the products prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 2 , wherein (a) is a scanning electron microscope (SEM) image of the RCF particles before carbonization, (b) is a scanning electron microscope (SEM) image of the high-fluidity negative carbon-assisted gelling material prepared in Example 1, and (c) is a scanning electron microscope (SEM) image of the negative carbon-assisted gelling material prepared in Comparative Example 1 by conventional wet carbonization.
[0076] from Figure 2 It can be seen that the surface of the uncarbonized RCF particles is amorphous, rough and contains a large number of original cracks; the surface of the high-fluidity negative carbon-assisted cementitious material prepared in Example 1 is smooth and flat, and the original cracks are repaired; the surface of the traditional wet-process carbonized negative carbon-assisted cementitious material prepared in Comparative Example 1 is covered with adsorbed calcite-type calcium carbonate.
[0077] The carbonization effect comparison results of Example 1 and Comparative Example 1 are shown in Table 2.
[0078] Table 2 Comparison of carbonization effects
[0079] Carbonization process Example 1 Comparative Example 1 Water consumption per kgRCF 0.1kg 5kg <![CDATA[CO2 concentration]]> 15% 15% Carbonization cycle 0.5h 1h <![CDATA[CO2 sequestration rate (wt.%)]]> 28.25% 30.38% Whether a dense calcium carbonate shell is formed yes no
[0080] Example 2
[0081] The same as Example 1, except that the ambient humidity during carbonization was controlled at 60%, and the preparation method of the wet RCF particles was different, specifically:
[0082] The construction demolition waste is crushed, magnetically separated, ground, and sieved to obtain RCF particles with a particle size of 48-75 μm, 75-150 μm, 150-270 μm, or 270-550 μm;
[0083] Deionized water and RCF particles (RCF particles with a particle size of 48-75 μm, 75-150 μm, 150-270 μm or 270-550 μm) were mixed at a liquid-to-solid ratio (mass ratio) of 1:10, and mechanically stirred to obtain wet RCF particles.
[0084] The comparison of carbonization effects is shown in Table 3.
[0085] Table 3 Comparison of carbonization effects
[0086]
[0087] Reducing the particle size of RCF particles increases the specific surface area, which in turn increases the carbonation level and CO2 storage efficiency, forming more calcium carbonate. However, when the particle size exceeds 150μm, the carbonation level and CO2 storage efficiency begin to decline rapidly. Therefore, it is recommended that RCF particles larger than 150μm be pre-ground to the target particle size.
[0088] Example 3
[0089] The same as Example 1, except that the humidity during carbonization is controlled at 60%, and the carbonization time is 10 min, 20 min, 30 min or 60 min.
[0090] The comparison of carbonization effects is shown in Table 4.
[0091] Table 4 Comparison of carbonization effects
[0092]
[0093] The above results show that increasing the carbonization time from 10 minutes to 60 minutes significantly increases the CO2 sequestration rate from 12.76 wt.% to 29.57 wt.%. The calcium carbonate formation rate (1.809 wt.% / min) reaches its peak at 30 minutes. These results indicate that 30 minutes is the optimal carbonization time, achieving a high level of carbonization in a relatively short period of time.
[0094] Effect Example 1
[0095] The particle size distributions of the RCF particles used in Example 1, the high-fluidity negative carbon-assisted gelling material prepared in Example 1, and the negative carbon-assisted gelling material prepared in Comparative Example 1 (i.e., the traditional wet negative carbon-assisted gelling material) are shown in FIG. Figure 3 .
[0096] The specific surface area of RCF particles was measured to be 304.3 m 2 / kg; the specific surface area of the high-fluidity negative carbon-assisted gelling material prepared in Example 1 is 81.61m 2 / kg; the specific surface area of the traditional wet negative carbon auxiliary cementitious material prepared in Comparative Example 1 is 353.4m2 / kg.
[0097] Effect Example 2
[0098] Flow properties:
[0099] Cement pastes were prepared using uncarbonized RCF particles (Table 1, particle size 48-75 μm), the highly fluid negative carbon auxiliary cementitious material prepared in Example 1, or the negative carbon auxiliary cementitious material prepared in Comparative Example 1, instead of P.O42.5 cement, at a water-cement ratio of 0.45. The expanded diameter (average value in two perpendicular directions) of the paste after 30 seconds of free flow was measured using a truncated cone die with an inner diameter of 70 mm and a height of 60 mm in accordance with GB / T 2419-2005. The results are shown in Table 5.
[0100] Table 5 Comparison of fluidity (mm)
[0101]
[0102] From the above results, it can be seen that when the content of uncarbonized RCF particles is 20%, the expansion diameter decreases by about 20%, which is attributed to its high porosity and strong water absorption of the amorphous phase.
[0103] When the content of the negative carbon auxiliary cementitious material prepared in Comparative Example 1 was 20%, the expansion diameter was reduced by about 26%.
[0104] When the content of the high-fluidity negative carbon auxiliary gelling material prepared in Example 1 is 20%, the expansion diameter increases by about 16%.
[0105] This result is consistent with the theory of calcium carbonate shell interface modification, confirming that the present invention reverses the negative impact of RCF incorporation on fluidity by constructing a "core-shell" structure, providing key technical support for the application of high-dosage solid waste-based cementitious materials.
[0106] Effect Example 3
[0107] Mechanical properties:
[0108] A four-component cement mortar system (mass ratio, water: P.O42.5 cement: GGBS (mineral powder): RCF = 0.35:0.45:0.4:0.15) was used to compare and analyze the effects of three types of RCF (uncarbonized RCF particles, the negative carbon auxiliary cementitious material prepared in Comparative Example 1, and the high-flow negative carbon auxiliary cementitious material prepared in Example 1) on the mechanical properties of the cement mortar system. The total RCF content was 15 wt.%, and the specimens were shaped into 40 × 40 × 40 mm. 3 Cube, standard curing conditions (20±2℃, RH≥95%), test compressive strength at 1d, 3d, 7d, 14d, and 28d. The results are shown in Table 6.
[0109] Table 6 Comparison of mechanical properties
[0110]
[0111] The improvement in early compressive strength of cement mortar is attributed to the carbonation-generated nano-calcium carbonate, which acts as a nucleation site and accelerates the hydration of C3S. The later increase in compressive strength is due to the reaction of calcite-type calcium carbonate with the aluminum in the cement to form Hc (hemicarbonate aluminate) and Mc (monocarbonate calcium aluminate), which inhibits the conversion of AFt (ettringite) to AFm (monosulfur calcium sulfoaluminate) and optimizes the pore structure.
[0112] From the above results, it can be seen that the high-fluidity negative carbon auxiliary cementitious material prepared by carbonization reconstruction provided by the present invention not only significantly improves the flow properties of the slurry, but also can maintain the mechanical properties without obvious decline, showing higher comprehensive application value in the field of green building materials.
[0113] The embodiments described above are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should fall within the scope of protection determined by the claims of the present invention.
Claims
1. A method for preparing a highly fluid negative carbon-assisted gelling material, characterized in that: The following steps are involved: The wet RCF particles are placed in an environment with a humidity of 60-80% and a CO2 concentration of 10-20 vol.%, and the wet RCF particles are carbonized in a suspended state by wind to obtain the high-fluidity negative carbon auxiliary gelling material.
2. The preparation method according to claim 1, characterized in that The moisture content of the wet RCF particles is 8 to 12 wt.%; And / or, the wind volume of the wind force is 100-300m 3 / h; And / or, the carbonization reaction time is 0.5 to 1 hour; And / or, the particle size of the RCF particles is ≤150 μm.
3. A high-fluidity negative carbon-assisted gelling material prepared by the preparation method according to any one of claims 1 to 2.
4. Use of the high-fluidity negative carbon auxiliary cementitious material according to claim 3 in concrete preparation.
5. A method for reducing the water absorption of RCF particles, characterized in that: The modification process of RCF particles includes the following steps: The wet RCF particles are placed in an environment with a humidity of 60-80% and a CO2 concentration of 10-20 vol.%, and the wet RCF particles are carbonized in a suspended state by wind.
6. A method for improving the fluidity of RCF particles, characterized in that: The modification process of RCF particles includes the following steps: The wet RCF particles are placed in an environment with a humidity of 60-80% and a CO2 concentration of 10-20 vol.%, and the wet RCF particles are carbonized in a suspended state by wind.
7. The method according to any one of claims 5 to 6, characterized in that: The moisture content of the wet RCF particles is 8 to 12 wt.%; And / or, the wind volume of the wind force is 100-300m 3 / h; And / or, the carbonization reaction time is 0.5 to 1 hour; And / or, the particle size of the RCF particles is ≤150 μm.
Citation Information
Patent Citations
Fluidization reaction device and method for efficiently mineralizing carbon dioxide by using solid waste
CN119633696A